2017
DOI: 10.1140/epjc/s10052-017-4986-3
|View full text |Cite
|
Sign up to set email alerts
|

A search for sterile neutrinos with the latest cosmological observations

Abstract: We report the result of a search for sterile neutrinos with the latest cosmological observations. Both cases of massless and massive sterile neutrinos are considered in the CDM cosmology. The cosmological observations used in this work include the Planck 2015 temperature and polarization data, the baryon acoustic oscillation data, the Hubble constant direct measurement data, the Planck SunyaevZeldovich cluster counts data, the Planck lensing data, and the cosmic shear data. We find that the current observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 115 publications
(108 reference statements)
3
43
0
Order By: Relevance
“…Besides, the positive correlation between the Hubble-Lemaître parameter and the interaction parameter, α, seems to indicate a possibility to relax the H 0 tension even more at the cost of assuming an energy flux from matter to dark energy (α > 0). When N eff is a free parameter of the model, the allowed interval of values shows a good agreement with previous ΛCDM analyses [6,73]. An important aspect worth mentioning is that the Λ(t)CDM + A l + N eff model allows at the same time for lower values of σ 8 and slightly higher values of H 0 with respect to the standard model and, therefore, offers a possibility to alleviate the H 0 -σ 8 tension discussed earlier (see eg.…”
Section: Analysis and Resultssupporting
confidence: 86%
“…Besides, the positive correlation between the Hubble-Lemaître parameter and the interaction parameter, α, seems to indicate a possibility to relax the H 0 tension even more at the cost of assuming an energy flux from matter to dark energy (α > 0). When N eff is a free parameter of the model, the allowed interval of values shows a good agreement with previous ΛCDM analyses [6,73]. An important aspect worth mentioning is that the Λ(t)CDM + A l + N eff model allows at the same time for lower values of σ 8 and slightly higher values of H 0 with respect to the standard model and, therefore, offers a possibility to alleviate the H 0 -σ 8 tension discussed earlier (see eg.…”
Section: Analysis and Resultssupporting
confidence: 86%
“…Since g * s (T dec ν ) = (11/2) + (7/4)N ν = 10.75, we need to compute the decoupling temperature T dec N to obtain g * s (T dec N ) and hence N eff . For 0.05 < ∼ N eff < ∼ 0.38 [139] we find 101 > ∼ g * s (T dec N ) > ∼ 22 and also T dec N ≃ 165 MeV to obtain g * s (T dec N ) ≃ 30 (which gives N eff = 0.25). To estimate T dec N , we compute the annihilation rate Ŵ N (T) of N ′ 1 at T, which is given by…”
Section: Dark Radiationmentioning
confidence: 68%
“…It has been recently suggested [131][132][133][134][135][136][137][138][139] that these tensions can be alleviated if the number N eff of the relativistic species in the young Universe is slightly larger than the standard value 3.046 and the mass of the extra relativistic specie is of O(0.1) eV [139]. Here we suggest a radiative generation mechanism of the neutrino mass, which is directly connected to the existence of a stable DM particle and also a non-zero N eff = N eff − 3.046.…”
Section: Model Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a series of studies have revealed that the properties of dark energy actually play an important role in cosmological measurement of neutrino mass . Moreover, the properties of dark energy also influence the cosmological search for sterile neutrinos [31][32][33][34][35][36]. It should also be mentioned that recent research has shown that the 10-year observation of gravitational-wave standard sirens from the Einstein Telescope (ET) can help improve the constraints on the total neutrino mass by about 10% [37] (see also Refs.…”
Section: Introductionmentioning
confidence: 99%